Analisa Kelayakan Investasi Kapal Katamaran Tipe Axe Bow Untuk Wisata Pulau Beting Aceh (Rupat) - Romadhoni Romadhoni; Budhi Santoso; Bobi Satria; Aprizawati Aprizawati; Supriyadi Supriyadi (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The AX BOW type catamaran is a ship that is used specifically for recreational purposes between Beting Aceh Island, which has two hulls or catamarans. This design aims to obtain data on ax bow type catamaran tourism boats that are suitable for the Aceh shoal island. This design is intended to see a good performance of resistance, stability, weight, and cost calculations. In this study, the authors analyzed the investment feasibility of the AX Bow catamaran, the main size of the ship, L = 12.20 m, B = 4.089 m, H = 1.48 m, T = 0.62 m, then the process of designing a landing craft boat using Maxurft Modeler Advance. The results of the investment feasibility analysis are declared feasible because the Net Present Value is 0.11% and Profitability Index > 0.11 with a break even point in 3 years of operation and an interest rate of 12% per year on capital loans. Keysword: AXE Bow, investment, tourism, Beting Aceh